PHYTOCHEMICAL PROFILING, GC/GC-MS ANALYSIS, AND ANTIBACTERIAL ACTIVITY OF DICHLOROMETHANE EXTRACT OF THE AERIAL PARTS OF TINOSPORA CRISPA - Muhammad Bilawal; Shamsuddin Bughio; Rehana Buriro; 4. Muhammad Imran Malik; 5. Shaheen Faizi (Journal of Animal and Plant Sciences, 2026)
Tinospora crispa is a medicinal plant, traditionally used for a wide range of pharmacological activities. This study conducted phytochemical screening, both qualitative and quantitative, of the non-polar dichloromethane (DCM) extract from the aerial parts of T. crispa, using gas chromatography-mass spectrometry (GC-MS) and antibacterial activity against Escherichia coli and Salmonella typhimuriumthrough agar well diffusion method. The analysis confirmed the presence of steroids, terpenoids, fatty acids, tannins, saponins, coumarins, carbohydrates, resins, alkaloids, glycosides, cardiac glycosides, and proteins. However, anthocyanins, leucoanthocyanins, and emodins were absent. The extract comprised a complex mixture of compounds, including oxygenated monoterpenes (e.g., 2-cyclohexen-1-one, 4-(3-hydroxybutyl)-3,5,5-trimethyl), long-chain ketones (e.g., 2-pentadecanone, 6,10,14-trimethyl), fatty acids (n-hexadecanoic and octadecanoic acids), and a variety of sterols and triterpenoids such as ethyl iso-allocholate, stigmasterol, α-amyrin, and betulin. Notably, a high relative abundance (43.85% area sum) of 6a,14a-methanopicene, perhydro-1,2,4a,6b,9,9,12a-heptamethyl-10-hydroxy was observed, suggesting that triterpenoids may contribute significantly to the pharmacological effects of the extract. The antibacterial activity of the DCM extract was determined against Escherichia coli and Salmonella typhimurium. Statistical analysis indicated that extract concentration significantly influenced antibacterial activity (p<0.005), with a concentration-dependent increase against both pathogenic bacteria. The extract produced inhibition zones of 15.6 ± 0.3 mm (6 µl) and 11.6 ± 0.3 mm (3µl) against S. typhimurium, whereas inhibited zones of 9.2 ± 0.0.1 mm (6 µl) and 3.9 ± 0.05 mm (3 µl) were observed against E. coli. These findings provide a comprehensive chemical characterization of T. crispa DCM extract and highlight its potential as a source of bioactive compounds with antibacterial activity, supporting its traditional medical application and source of novel therapeutic agents.
Keywords: Antibacterial activity; Dichloromethane extract; Phytochemical profiling; Tinospora crispa; GC/GCMS; Aerial plant